Maillard reactions of dextrins and starch - Kramhöller, Barbara; Pischetsrieder, Monika; Severin, Theodor (Zeitschrift für Lebensmittel-Untersuchung und -Forschung, 1993)
When dextrins or starch are heated with propyl-amine in neutral aqueous solution at 100-130° C a brown colouration is observed. From the reaction mixture 3-hydroxy-2-methyl-1-propyl-4(1H)-pyridone 11, 1,4-dihy-dro-2-methyl-1-propyl-4-propylimino-3-pyridinol 12 and 5-hydroxymethyl-1-propyl-pyrrol-2-aldehyde 13 can be extracted with organic solvents and separated by HPLC. Enzymatic hydrolysis effects the release of 1(3-hydroxy-1-propyl-2-pyrrolyl)-1-ethanone 10 from a glycosidically bound precursor.
UnivIS-Import:2015-03-05:Pub.1993.nat.dchph.llmch.mailla